Effect of ginkgo diterpene lactone meglumine on the quality of life in patients with acute ischemic stroke - Xue Tian; Qin Xu; Xue Xia; Yijun Zhang; Xingquan Zhao; Anxin Wang (Health and Quality of Life Outcomes)
Abstract Objective Ginkgo diterpene lactone meglumine (GDLM) could improve the functional outcome after acute ischemic stroke (AIS). This study aimed to investigate the efficacy of GDLM on the quality of life in patients with AIS in China. Methods This is a post hoc analysis of Efficacy and Safety of Ginkgo Diterpene Lactone Meglumine in Acute Ischemic Stroke trial. The quality of life was measured using the EuroQoL questionnaire, including EQ-5D and EQ visual analogue scale (EQ-VAS). The primary outcomes were changes in EQ-5D and EQ-VAS from baseline to day 14 and day 90 after randomization. Results A total of 3219 patients with completed data on outcomes were enrolled, with median age of 63 years (interquartile range, 55–70) and 2,067 (64.2%) men. GDLM was associated with a significant decrease in scores of ED-5Q components (from 0 [no problem] to 3[extreme problem]), the mean difference between GDLM and placebo group was -0.14 for mobility, -0.11 for usual activities and self-care, -0.09 for pain/discomfort, and -0.34 for anxiety/depression on day 14, respectively. Similar results were observed on day 90. Additionally, there was statistically significant difference of changes in EQ-VAS between the GDLM group and the placebo group from baseline to day 14 (mean difference, 1.70; 95% confidence interval [CI], 0.78–2.62; P = 0.0003) and to day 90 after randomization (mean difference, 3.29; 95% CI, 2.37–4.22; P < 0.001). Conclusions In this analysis of Chinese patients with AIS, GDLM could improve the 14-day and 90-day quality of life compared with the placebo. Trial registration URL: https://www.clinicaltrials.gov . Unique identifier: NCT02526225. Registration Date: 2016–02-01.